2009
DOI: 10.1002/adsc.200800801
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Enantioselective Hydrosilylation of Ketones Catalyzed by Zinc‐Macrocyclic Oligoamine Complexes

Abstract: Chiral macrocyclic tetra-and hexamine macrocycles derived from trans-1,2-diaminocyclohexane (DACH) in complexes with diethylzinc efficiently catalyze the asymmetric hydrosilylation of aryl alkyl ketones with enantiomeric excess of the product up to 89%. The cyclic structure of the trianglamine ligand increases the enantioselectivity of the reaction, in comparison to the catalysis with the acyclic N,N'-dibenzyl-DACH ligand. Density functional theory (DFT) computations on the structures of ligand-zinc complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…[9][10][11] In a previous paper, 11 we showed zinc salts to be very effective catalysts for the hydrosilylation of ketones. Interestingly, when chalcone was used as a carbonyl substrate under similar conditions, the carbonyl group was reduced to a methylene unit.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] In a previous paper, 11 we showed zinc salts to be very effective catalysts for the hydrosilylation of ketones. Interestingly, when chalcone was used as a carbonyl substrate under similar conditions, the carbonyl group was reduced to a methylene unit.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to the high price and the toxicity less expensive and low toxic metals are highly requested for replacement [36]. Here the use of zinc is probably of great interest [37][38][39][40][41][42][43][44][45][46][47][48][49]. Although several research groups demonstrated the abilities of zinc catalysts in the reduction of imines [50][51][52][53], reductive amination protocols are scarcely reported [54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] We [24] and others [28] have recently reported that chiral hexamine macrocycles (trianglamines) [29] derived from DACH, in complexes with diethylzinc, efficiently cata-lyze asymmetric hydrosilylation of aryl alkyl ketones with enantiomeric excess of the product of up to 89 %. [24][25][26][27] We [24] and others [28] have recently reported that chiral hexamine macrocycles (trianglamines) [29] derived from DACH, in complexes with diethylzinc, efficiently cata-lyze asymmetric hydrosilylation of aryl alkyl ketones with enantiomeric excess of the product of up to 89 %.…”
Section: Introductionmentioning
confidence: 99%
“…[2a,22c,24] Because the reaction mechanism is highly dependent on the catalytic system, the presence of any additive, and the nature of the solvent, the originally proposed mechanism for [Zn(diamine)]-catalyzed hydrosilylation [2a] may not be the same as those proposed for the reactions carried out in the presence of an alcohol. [24,40,44] To this end, we carried out experimental and theoretical studies on the mechanism of [Zn(diamine)-(diol)]-catalyzed hydrosilylation of prochiral ketones, based on NMR and electronic circular dichroism (ECD) measurements as well as on DFT calculations of the possible pathways of reaction. [24,40,44] To this end, we carried out experimental and theoretical studies on the mechanism of [Zn(diamine)-(diol)]-catalyzed hydrosilylation of prochiral ketones, based on NMR and electronic circular dichroism (ECD) measurements as well as on DFT calculations of the possible pathways of reaction.…”
Section: Introductionmentioning
confidence: 99%